Effect of observation on lower limb prosthesis gait biomechanics: Preliminary results. (December 2016) - Malchow, Connor; Fiedler, Goeran
Background: The Hawthorne effect, a subcategory of reactivity, causes human behavior to change when under observation. Such an effect may apply to gait variation of persons with prosthetics or orthotics devices. Objectives: This study investigated whether the presence of observers directly affects the gait pattern of users of lower limb prostheses. Study design: Within-subject intervention study. Methods: Primary outcome measures were gait parameters of initial double support time and upper body lateral tilt angle, which were collected with a mobile sensor attached to the subjects' back. To make subjects feel unwatched, a certain amount of deception was necessary, and two different conditions were created and statistically compared against each other: one in which the subjects were initially unaware of the attention of observers and another one in which the same subjects were aware of a group of observers. Results: Data from two subjects using trans-femoral prosthesis are reported. Findings included a change in step initial double support percentage by up to 14.2% ( p = 0.019). Considerable changes were also noted in secondary outcome measures including speed, stride length, and stride symmetry. Conclusions: A reactivity effect of observation exists in prosthetics gait analysis. More comprehensive studies may be motivated by these preliminary findings. Clinical relevance: Results of this study suggest that users of lower limb prostheses walk differently when their gait is being assessed (e.g. in the prosthetist's office) than in situations without observers. This may in part explain the clinical experience that modifications of prosthetic fit or alignment provide only short-term betterment.